Cervical Thymic Cyst: A Rare Differential Diagnosis in Lateral Neck Swelling - Vijendra Shenoy; M. Panduranga Kamath; Mahesh Chandra Hegde; Raghavendra Rao Aroor; Vijetha V. Maller (Case Reports in Otolaryngology)
Introduction. Thymic cysts are among the rarest cysts found in the neck. Nests of thymic tissue may be found anywhere along the descent of the thymic primordia from the angle of the mandible to the mediastinum. Mediastinal extension is seen in 50% of cervical thymic cysts. Case Report. We report an uncommon case of a 15-year-old male, who noted a painless, growing mass on left side of his neck of one-year duration. Computerised tomographic scan showed a multiloculated fluid density lesion with enhancing septae in the left parapharyngeal space, extending from the level of mandible up to C7 vertebral level. Here, we discuss the surgical aspect, histopathology, and management of this rare lateral neck swelling. Discussion. Clinically, in most cases, cervical thymic lesions present as a unilateral asymptomatic neck mass, commonly on the left side of the neck, and 75% of patients present before 20 years of age. Conclusion. Thymic cyst should be included as differential diagnosis of cystic neck masses. Greater awareness among the pathologists may decrease misdiagnosis.